Wear behavior of tribologically optimized tool surfaces for incremental forming processes. (December 2016) - Sieczkarek, P.; Wernicke, S.; Gies, S.; Tekkaya, A.E.; Krebs, E.; Wiederkehr, P.; Biermann, D.; Tillmann, W.; Stangier, D.
Abstract: The mechanical wear behavior of forming tools is the limiting factor during an incremental gear-forming process. These forming tools with a simply shaped geometry are exposed to high forming forces. Additionally, the necessary workpiece chambering, which is characteristic for this incremental process restricts the dimensioning of the tools. Thereby, the geometrical design of the forming tools is limited, which leads to a decreased lifetime. Functional structures on the tool surfaces can influence the occurring loading and wear behavior by reducing the contact area, the supply of lubricant pockets, and by a controlled influence and adjustment of the occurring material flow. For the extension of the tool's lifetime, different surface concepts and combinations with CrAlN PVD-coatings are investigated. To offer conditions with a high tool load, the investigations are focused on an incremental gear forming process with a simple one-wedge forming tool. The results show abrasive and adhesive wear characteristics, as well as outbreaks, and crack formations. The crack propagation on the flank leads to a chipping of the tool tip, hence limiting the tool life. Compared to the reference tool, a surface structure combined with a PVD-coating provides a significant increase of the tool life of 84%. Highlights: Experimental analysis of tool life and wear mechanisms in an incremental gear forming process. Modification of tool surfaces using complex surface structures and PVD-coating technology. Micromilling of bionically-inspired structures in hardened high-speed steel ASP ® 2023 (>60 HRC). Successful combination of surface structures and wear resistant CrAlN PVD-coating. Despite the high mechanically sensitivity of the surface structure, the PVD-coating provides a good protection of the surface and a significant longer tool life (84%).